The Immunopathogenesis of Neuroinvasive Lesions of SARS-CoV-2 Infection in COVID-19 Patients - Alipoor, Shamila D.; Mortaz, Esmaeil; Varahram, Mohammad; Garssen, Johan; Adcock, Ian M. (Frontiers in Neurology, 2021)
The new coronavirus disease COVID-19 was identified in December 2019. It subsequently spread across the world with over 125m reported cases and 2.75M deaths in 190 countries. COVID-19 causes severe respiratory distress; however, recent studies have reported neurological consequences of infection by the COVID-19 virus SARS-CoV-2 even in subjects with mild infection and no initial neurological effects. It is likely that the virus uses the olfactory nerve to reach the CNS and that this transport mechanism enables virus access to areas of the brain stem that regulates respiratory rhythm and may even trigger cell death by alteration of these neuronal nuclei. In addition, the long-term neuronal effects of COVID-19 suggest a role for SARS-CoV-2 in the development or progression of neurodegerative disease as a result of inflammation and/or hypercoagulation. In this review recent findings on the mechanism(s) by which SARS-CoV-2 accesses the CNS and induces neurological dysregulation are summarized.